THE IMPORTANCE OF INCLUSIVE EDUCATION IN THE PROCESS OF CONTINUOUS PROFESSIONAL DEVELOPMENT - Rizayeva Shalola Mamir qizi (Web of Journals Publishing, 2023)
This article provides information about continuing education, its principles, professional development of continuing professional development through the continuing professional education platform, and the importance of inclusive education in the process of continuing professional development.
Keywords: Inclusive education, continuous professional development, principles of inclusive education, professional competence.